Machinima: Extending brand reach. Issue 6 (4th November 2015) - Harwood, Tracy; Garry, Tony; Uwins, Mike
Abstract: The paper presents findings of an empirical qualitative investigation into the role of machinima (machine‐cinema) in extending the brand reach of game developers' market propositions, drawing on participation, co‐creation and immaterial labour literature. Machinima is a contemporary Internet cultural phenomenon, whereby firms' 'super' customers create original works from game assets beyond that of merely gameplay. Interestingly, firms' marketing strategies are evidently focussed on traditional channels with apparently little emphasis given to Internet born cultures such as machinima, which now has massive global following. Thus, the resultant user‐generated content, which may be subsequently adapted and further distributed by other customers, is harnessed by firms, effectively exploiting the prowess of the community of games players to market their endeavours as advertising and product development. Copyright © 2015 John Wiley & Sons, Ltd.